Performance evaluation of mechanized shelling machine for steam treated raw cashewnuts - Balasubramanian, D.; Lyra Kokila, Joycy Rodrigues (Journal of Plantation Crops, 2014)
Shelling is the process of extracting edible cashew kernel from pre-treated raw cashewnuts. Manual cracking of drum roasted nuts using mallet is the oldest method followed in India. A hand-cum-pedal operated shelling gadget is predominantly used for extraction of cashew kernel from steam treated nuts. Extraction of whole kernels is the ultimate aim in cashewnut processing as it fetches premium price in the market. About 13.39 lakh MT of raw cashewnuts were processed in the cashew processing facility developed in India during the year 2010-11. In order to overcome the problem of labour scarcity, mechanized shelling machine is introduced in processing for cashew. In this study performance of the mechanized shelling machine in terms of operational capacity, shelling efficiency, whole kernel recovery and kernel intact were analysed. Shelling was performed in three different modes viz., manual, mechanical (Auto Feed) and mechanical (Manual Feed) and compared. On an average operational capacity was found to be 8.07, 11.39 and 9.25 kg h–1 irrespective of the size of the nuts for three different methods of shelling investigated. Time taken to manipulate the size, proper positioning of nut and application of force to penetrate the blades in to the shell without damaging the kernel are the major factors influencing the manual shelling process. Channel design to position the nuts and precise adjustments of shoe movement for shelling are the principal reasons for increased operational capacity. Although whole kernel recovery found to be non-significant, Mechanical (Manual Feed) showed better results (95.63%) than other two methods employed. Manual system showed better shelling efficiency due to constant attention of person operating with the shelling unit. Mechanical system recorded 18.98 per cent of kernel intact which is 37.9 per cent lower than manual method. Cost of production reveals that mechanical system is 5.16 times superior to manual method of shelling.